H[the sign of infinity] control of discrete-time linear systems constrained in state by equality constraints - Filasová, Anna; Krokavec, Dušan (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, stabilizing problems in control design are addressed for linear discrete-time systems, reflecting equality constraints tying together some state variables. Based on an enhanced representation of the bounded real lemma for discretetime systems, the existence of a state feedback control for such conditioned stabilization is proven, and an LMI-based design procedure is provided.
Keywords: equality constraints; discrete-time systems; linear matrix inequality; state feedback; control algorithms; quadratic stability; singular systems